Mapping Pentahelix Collaboration for Human Resource Development of Micro, Small, and Medium Enterprises: A Bibliometric Analysis - Lesi Oktiwanti; Wiwin Herwina; Agus Sumantri; Najwa Nurshadrina; Intan Aolia (Jurnal Pemberdayaan Masyarakat, 2025)
This article examines the role of pentahelix collaboration in promoting human resource development (HRD) for micro, small, and medium enterprises (MSMEs) using a bibliometric approach. Using 180 Scopus-indexed publications from 2016 to 2025, data were processed with VOSviewer to examine publication trends, co-authorship networks, keyword clustering, and thematic development. The findings indicate that Indonesia contributes the largest number of studies, reflecting its central role in the pentahelix-based development discourse. Five thematic clusters were identified, covering institutional collaboration, digitalization, education, cultural values, village empowerment, and collaborative governance. The results show a gradual shift from conceptual discussions to practical applications, particularly in digital transformation and inclusive governance for MSMEs. Emerging themes such as sustainability, women’s empowerment, and ecosystem-based innovation are gaining significant attention. This study contributes theoretically by refining the conceptual framework of pentahelix collaboration in relation to HRD, while practically providing direction for policymakers, educators, and practitioners to strengthen MSME competitiveness through inclusive and adaptive strategies. By mapping the research landscape, this study highlights the importance of multi-stakeholder collaboration as a foundation for building resilient and innovation-driven MSME ecosystems.